1997
DOI: 10.1068/a291243
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Elderly People to Join Existing Households: Some Evidence from the 1991 Household Sample of Anonymised Records

Abstract: In this paper the extent to which migration of the elderly is linked to changing family living situations is explored. The work described is part of a larger project concerned with the relationship between migration, kinship, and household change. Discussions of the living arrangements of older people have often referred to moves made to join adult children or other relatives. In this paper we use the Household Sample of Anonymised Records to investigate moves of this type. The Sample of Anonymised Records al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Nearly 60% of the widows reside all year in an extended household compared to 18% of the married couples and neither of the single men (though both of these men still reside with young, unmarried daughters). This finding is supported by other studies, such as Al-Hamad, Flowerdew, and Hayes (1997), who concluded in their study of elderly who migrate to join existing households in England that bereavement was likely to precipitate such a move. Also, Table 3 shows that only one elderly, a widow, lives with her daughter and that is only when she is in Istanbul.…”
Section: Journal Of Agingsupporting
confidence: 81%
“…Nearly 60% of the widows reside all year in an extended household compared to 18% of the married couples and neither of the single men (though both of these men still reside with young, unmarried daughters). This finding is supported by other studies, such as Al-Hamad, Flowerdew, and Hayes (1997), who concluded in their study of elderly who migrate to join existing households in England that bereavement was likely to precipitate such a move. Also, Table 3 shows that only one elderly, a widow, lives with her daughter and that is only when she is in Istanbul.…”
Section: Journal Of Agingsupporting
confidence: 81%
“…Changes in household composition in situ are relatively rare (Hayes & Al‐Hamad, 1997; Jackson et al., 1991; Lichtenberg, MacNeill, & Mast, 2000; Mutchler & Burr, 1991; Pendry, Barrett, & Victor, 1999). Exceptions include several studies of incident intergenerational co‐residence (Al‐Hamad, Flowerdew, & Hayes, 1997; Mickus, Stommel, & Given, 1997; Roan & Raley, 1996; Speare, Avery, & Lawton, 1991; Worobey & Angel, 1990a), and life years of co‐residence (Schoeni, 1998). Although the unit of observation in studies of changing living arrangements is usually the older individual, some studies observe households making changes as a unit (Clark & Knapp, 1996; De Jong, Warland, & Root, 1998; Lin, 1997; Lu, 1998; Robison & Moen, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The most potent push factors include the death of a spouse and abrupt changes in income or employment, usually retirement. Health‐related events, such as recent hospitalization, short‐term nursing home admissions, or a sharp increase in outpatient visits, influence housing choices (Al‐Hamad et al., 1997; Chevan, 1995; Choi, 1996c; Colsher & Wallace, 1990; Cuba & Longino, 1991; Davis et al., 1996; De Jong, Wilmoth, Angel, & Cornwell, 1995; Forbes et al., 1997; Kan, 1999; Mickus et al., 1997; Mutchler, 1992; Mutchler & Burr, 1991; Roan & Raley, 1996; Robison & Moen, 2000; Silverstein, 1995; Spitze, Logan, & Robinson, 1992; Wolinsky et al., 1992). Recent changes in functional status also serve to destabilize households (Al‐Hamad et al., 1997; Anderson, James, Miller, Worley, & Longino, 1998; Angel et al., 1992; Bradsher, Longino, Jackson, & Zimmerman, 1992; Choi, 1996c; De Jong et al., 1995; Jackson et al., 1991; Longino et al., 1991; Miller, Longino, Anderson, James, & Worley, 1999; Silverstein, 1995; Speare et al., 1991; Spitze et al., 1992; Worobey & Angel, 1990a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual, household, and social factors all have impacts on older people's relocation behavior. Older people's individual characteristics and socioeconomic status, such as age, gender, educational level, health status [9], economic status [10], and marital status [11,12] were identified to affect older people's relocation [13]. One important factor of the location choice for relocation by older people is the living distance from their adult children and friends, which has impacts on the convenience for taking care of their grandchildren, receiving care support from family members or social networking [14].…”
Section: Elderly Relocationmentioning
confidence: 99%